LEVELS OF PATIENTS EXPOSURE AND A POTENTIAL FOR OPTIMIZATION OF THE PET DIAGNOSTICS IN THE RUSSIAN FEDERATION - L. A. Chipiga; I. A. Zvonova; D. V. Ryzhkova; M. A. Menkov; М. B. Dolgushin (Радиационная гигиена)
This study presents an overview of the most common positron emission tomography examinations in Russia, as well as the acquisition protocols and patient doses. The data collection was performed in 2012–2017 in 19 positron emission tomography departments in 12 regions of the Russian Federation by questioning the staff. The majority of the Russian positron emission tomography departments were equipped by modern positron emission tomography scanners combined with computed tomography. In each investigated department, data on all types of positron emission tomography examinations, radiopharmaceuticals, administered activities used for standard patient (body mass 70±5 kg) and parameters of computed tomography protocols was collected. The effective doses of patients from combined positron emission computed tomography examinations were estimated as a sum of the dose from the internal exposure (injected radiopharmaceutical) and the external exposure (computed tomography scan). Whole body positron emission tomography examinations in Russia were commonly performed with 18F-fluorodeoxyglucose (18F-FDG), 18F-choline, 11С-choline, 68GaPSMA, 68Ga-DOTA-TATE, 68Ga-DOTA-NOC, brain examinations – 18F-FDG, 11С-metionine, 18F-choline, 18F-tyrosine, myocardial perfusion – 13N-ammonie.The highest patient effective doses (about 17 mSv) were observed for whole-body positron emission computed tomography examinations; for brain examinations – 3,4 – 4,8 mSv; for myocardial perfusion – 2,8 mSv. The computed tomography scan contributes up to 65 – 95% to the total patient effective dose for whole body examinations; 20 – 30% for head examinations. For the multiphase computed tomography scan effective doses may be increased to: 15 mSv for head examinations, 25 – 30 mSv for whole body examinations and 35 – 40 mSv for myocardial examinations. A standardization of acquisition and processing protocols is necessary for optimization of positron emission tomography examinations in Russia and for the intercomparison of results obtained in different positron emission tomography departments. Low dose computed tomography protocols, justification of diagnostic and multiphase computed tomography protocols, application of tube current modulation system and modern reconstruction algorithms, education and training of the staff in the field of radiation protection should be used for optimization of radiation protection of patient.